2018
DOI: 10.1016/j.syapm.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Geodermatophilus chilensis sp. nov., from soil of the Yungay core-region of the Atacama Desert, Chile

Abstract: A polyphasic study was undertaken to establish the taxonomic status of three representative Geodermatophilus strains isolated from an extreme hyper-arid Atacama Desert soil. The strains, isolates B12, B20 and B25, were found to have chemotaxonomic and morphological properties characteristic of the genus Geodermatophilus. The isolates shared a broad range of chemotaxonomic, cultural and physiological features, formed a well-supported branch in the Geodermatophilus 16S rRNA gene tree in which they were most clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 93 publications
0
12
0
1
Order By: Relevance
“…Members of the family Geodermatophilaceae have received the most attention, notably the genera Blastococcus, Geodermatophilus and Modestobacter ; members of these taxa are known to be resistant to desiccation, ionizing radiation, UV‐light and heavy metals (Sghaier et al ). Dereplicated Geodermatophilaceae strains from Atacama Desert habitats have been validly named as Blastococcus atacamensis (Castro et al ), Geodermatophilus chilensis (Castro et al ) and Modestobacter caceresii (Busarakam et al ) and shown to have moderately large genomes (3·9–5·9 Mb). Representatives of these taxa not only contain NP‐BGCs but also stress‐related genes that encode for properties such as carbon starvation, temperature fluxes, osmotic stress and UV‐light.…”
Section: Desertsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of the family Geodermatophilaceae have received the most attention, notably the genera Blastococcus, Geodermatophilus and Modestobacter ; members of these taxa are known to be resistant to desiccation, ionizing radiation, UV‐light and heavy metals (Sghaier et al ). Dereplicated Geodermatophilaceae strains from Atacama Desert habitats have been validly named as Blastococcus atacamensis (Castro et al ), Geodermatophilus chilensis (Castro et al ) and Modestobacter caceresii (Busarakam et al ) and shown to have moderately large genomes (3·9–5·9 Mb). Representatives of these taxa not only contain NP‐BGCs but also stress‐related genes that encode for properties such as carbon starvation, temperature fluxes, osmotic stress and UV‐light.…”
Section: Desertsmentioning
confidence: 99%
“…Another important development is the realization that in some actinobacterial taxa, such as the genera Amycolatopsis , Frankia and Micromonospora , there is a link between the distribution of NP‐BGCs and phylogeny (Adamek et al ; Carro et al ; Nouioui et al ). In addition, information drawn from whole‐genome sequences is providing fascinating insights into how micro‐organisms adapt to extreme habitats, as witnessed by the ability of members of the actinobacterial family Geodermatophilaceae to withstand extreme environmental conditions that prevail in hyperarid desert habitats (Castro et al , b).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, many of the stress related genes were shown to be linked with carbon starvation, oxidative and osmotic stress, resistance to UV radiation and temperature fluxes, as exemplified by genes encoding for carbon starvation protein A (CstA), which promotes peptide uptake [72][73][74]; sox genes associated with responses to oxidative stress [75,76]; KatE and uvrD genes linked to protection against reactive oxygen and UV-radiation [77]; dnaK and dnaJ, hrcA, grpE and Hsp genes related to responses to heat shock [78]; a family of proteins associated with cold shock responses [79] and coxE, coxD and coxG genes along with a coxSML cluster coding for utilisation of carbon monoxide indicating that the isolate may have a chemolithoautotrophic lifestyle [80]. Similar patterns of stress-related genes have been detected in the genomes of the type strains of the B. atacamensis [16], G. chilensis [17], M. caceresii [10] and 'M. excelsi' [3].…”
mentioning
confidence: 55%
“…excelsi' are rich in stress genes that provide an insight into how these organisms have adapted to the prevailing environmental conditions in hyper-arid Atacama Desert soils [3,10]. Moreover, genomes of representative type strains of the family Geodermatophilaceae revealed many biosynthetic gene clusters (BGCs) related to the biosynthesis of secondary metabolites, as exemplified by the genomes of the type strains of Blastococcus atacamensis [16], Geodermatophilus chilensis [17], M. caceresii [10] and 'M. excelsi' [3].…”
mentioning
confidence: 99%
“…The sequences of the nearest type species for each isolate were retrieved from GenBank (Benson et al, 2017). Phylogenetic analyses were carried out after Castro et al (2018); phylogenetic trees were inferred with MEGA software version 7.0 (Kumar et al, 2016). The bacterial strains were deposited in the Chilean Collection of Microbial Genetic Resources (http://www.cchrgm.cl) with the following access codes RGM 2525, RGM 2526 and RGM 2607.…”
Section: Molecular Identification Of Selected Bacteria and Bioinformamentioning
confidence: 99%